Preparation method of nano boron nitride / epoxy resin composite material with electric field induced boron nitride nanosheet orientation
By applying a DC electric field during the curing process of the nanoboro nitride/epoxy resin composite, the arrangement of boron nitride nanosheets is induced, combined with the use of planetary hybrid equipment and amide-based amine curing agent, the problem of increasing the thermal conductivity of composite materials in traditional methods is solved, and efficient thermal conductivity improvement and dielectric performance optimization are achieved.
Patent Information
- Application Number
- CN202310063041.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-01-20
AI Technical Summary
While increasing the content of boron nitride particles, the traditional method makes it difficult for the mixture to stir, disperse and cure, and cannot effectively improve the thermal conductivity of the composite material.
By applying a DC electric field during the material curing process, the boron nitride nanosheets are induced to arrange in the direction of the electric field to form a heat conduction channel. Combined with the stirring dispersion of the planetary mixing equipment and the use of amide amine curing agent, the efficient preparation of the nanoboro nitride/epoxy resin composite material is achieved.
At the lower boron nitride content, the thermal conductivity and relative dielectric constant of the composite material are significantly improved, the thermal resistance of the material is reduced, the preparation process is simplified, and the insulation strength of the material is ensured.
Smart Images

Figure CN116041909B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a nano boron nitride / epoxy resin composite material, in particular to a method for preparing an epoxy resin composite material which realizes orientation of boron nitride nanosheets with a higher content through direct current electric field induced curing. Background Art
[0002] Pure epoxy resin, as a thermosetting material with good chemical stability and excellent insulation performance, is widely used in power electronic device substrate materials and power system insulation. With the development of modern times, the requirements for insulation materials in terms of electrical resistance and heat dissipation are getting higher and higher. It is no longer possible to achieve the expected goals by simply using pure epoxy resin to achieve material insulation. Boron nitride has a high thermal conductivity and a low dielectric constant, and is very suitable for adding to epoxy resin to improve the electrical properties of the material.
[0003] In order to significantly improve the thermal conductivity of the composite material, a high content of boron nitride particles needs to be added to the epoxy resin. However, this traditional method of improving thermal conductivity will make the mixture difficult to stir, disperse and cure while increasing the content of boron nitride particles. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a method for preparing a nano boron nitride / epoxy resin composite material with boron nitride nanosheet orientation. By applying a certain DC electric field during the curing process of the material, the boron nitride nanosheets are induced to gradually tend to be arranged along the direction of the electric field, so that they form a heat-conducting channel bridge, which is approximately close to the thickness direction of the composite material. The shorter the heat conduction path along the thickness direction, the lower the thermal resistance, and the thermal conductivity of the material can be fully improved when the boron nitride content is low.
[0005] The present invention provides a method for preparing a nano boron nitride / epoxy resin composite material with electric field induced boron nitride nanosheet orientation, which is achieved by dispersing nanoparticles through a planetary mixing device, inducing the orientation of the nanoparticles through an electric field, and heating and curing the composite material, and specifically comprises the following steps:
[0006] S1: using a planetary mixing device to stir and disperse the mixture of nano boron nitride and epoxy resin;
[0007] S2: adding a curing agent to the stirred and dispersed mixture of nano boron nitride and epoxy resin, performing vacuum degassing and placing the mixture in a mold;
[0008] S3: The arrangement direction of the boron nitride nanosheets in the mixture is regulated by a direct current electric field during the curing process. At the same time, the mold is placed in a vacuum oven and heated to accelerate the curing process.
[0009] Preferably, in step S1, the content of nano-boron nitride is 15-25wt%; the mixture of nano-boron nitride particles and epoxy resin is stirred and dispersed multiple times by using a planetary mixing device combining revolution and rotation: stirring from slow to fast for 1-5min, 1-5min, 2-10min at a speed of 400-600r / min, 800-1200r / min, 1500-3000r / min, respectively, so that the nano-boron nitride particles can be evenly dispersed in the epoxy resin. More preferably, the content of nano-boron nitride is 25wt%; stirring from slow to fast for 3min, 3min, 6min at a speed of 500r / min, 1000r / min, 2000r / min, respectively, so that the nano-boron nitride particles can be evenly dispersed in the epoxy resin.
[0010] Preferably, in step S2, the curing agent is a combination of one or two of EPIKURE 3046 amidoamine curing agent and EPIKURE 3072 amidoamine curing agent. After adding the curing agent, stir at a speed of 1500 to 3000 r / min for 2 to 10 min, and then perform vacuum degassing, and the time of vacuum degassing is 20 to 60 min. More preferably, the curing agent is EPIKURE 3046 amidoamine curing agent. After adding the curing agent, stir at a speed of 2000 r / min for 6 min, and then perform vacuum degassing, and the time of vacuum degassing is 30 min. The amidoamine curing agent used in the present invention can cross-link with the epoxy group in the epoxy resin to form a stable three-dimensional network structure that is not easily dissolved and dissolved, so that the defects in the composite material are as few as possible, so its dielectric constant is relatively high, and the curing agent can promote the BN in the epoxy resin to form a heat-conducting chain, thereby reducing the thermal resistance of the composite material and improving its thermal conductivity.
[0011] Preferably, in step S3, during the curing process of the nano-boron nitride / epoxy resin composite material, copper electrodes with a spacing of 1 to 10 mm are placed inside the mold, and a direct current voltage is applied to the electrodes to achieve the alignment and orientation of the boron nitride nanosheets in the composite material in the direction of the electric field intensity. More preferably, the spacing of the copper electrodes placed inside the mold is 3 mm.
[0012] Preferably, in step S3, the heating temperature of the vacuum oven is 50-100° C., and the heating time is 10-30 hours. More preferably, the heating temperature of the vacuum oven is 80° C., and the heating time is 20 hours.
[0013] In summary, the present invention has the following beneficial effects: by using a planetary mixing device to stir and disperse nanoparticles multiple times, adding a curing agent with better curing performance, using electric field to induce nanoparticle orientation, and heating to cure the composite material, four core process steps are used together to obtain a raw material that is easy to stir under a high BN content (25%), and by electric field orientation, a composite material with higher thermal conductivity and higher relative dielectric constant is formed. Specifically, (1) the nanoparticles are stirred and dispersed multiple times by a planetary mixing device, making the raw material easier to stir; (2) by adding a curing agent with better curing performance, the defects in the composite material are reduced and the dielectric constant is improved. At the same time, the curing agent can promote the BN in the epoxy resin to form a thermal conductive chain, thereby reducing the thermal resistance of the composite material and improving its thermal conductivity; (3) by inducing the internal boron nitride nanosheets along the electric field direction during the curing process of the composite material through a DC electric field, the thermal conductivity in this direction is improved, and the thermal conductivity is greatly improved, thereby reducing the difficulty of preparing the material under high thermal conductivity requirements and ensuring the insulation strength of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Flow chart for the preparation of nano-boron nitride / epoxy resin composites with oriented boron nitride nanosheets.
[0015] Figure 2 Diagram of the preparation model of nano-boron nitride / epoxy resin composite materials with oriented boron nitride nanosheets. DETAILED DESCRIPTION
[0016] The following is a detailed and complete description of the embodiments of the present invention. The examples described below are not all embodiments of the present invention, but only some embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by other technicians in the field without creative work are within the scope of protection of the present invention.
[0017] Example 1
[0018] S1: Using a planetary mixer to stir and disperse the mixture of nano boron nitride and epoxy resin. The content of nano boron nitride is 25wt%; using a planetary mixer that combines revolution and rotation to stir and disperse the mixture of nano boron nitride particles and epoxy resin for multiple times: stirring at a speed of 500r / min, 1000r / min, and 2000r / min from slow to fast for 3min, 3min, and 6min respectively so that the nano boron nitride particles can be evenly dispersed in the epoxy resin.
[0019] S2: Add curing agent to the stirred and dispersed mixture of nano boron nitride and epoxy resin, perform vacuum degassing and place in a mold. The curing agent is EPIKURE 3046 amidoamine curing agent. After adding the curing agent, stir at a speed of 2000r / min for 6 minutes, and then perform vacuum degassing. The uniformly dispersed mixture is degassed by vacuuming. The vacuum degassing time is 30 minutes. During the degassing process, appropriate air can be released to prevent the mixed liquid from expanding too much and overflowing the container.
[0020] S3: The arrangement direction of the boron nitride nanosheets in the mixture is regulated by a direct current electric field during the curing process. At the same time, the mold is placed in a vacuum oven for heating to accelerate the curing process. During the curing process of the nano-boron nitride / epoxy resin composite material, copper electrodes with a spacing of 3 mm are placed inside the mold, and a direct current voltage is applied to the electrodes to achieve the arrangement and orientation of the boron nitride nanosheets in the composite material in the direction of the electric field intensity; the heating temperature of the vacuum oven is 80°C, and the heating time is 20 hours.
[0021] Example 2
[0022] The specific steps of the preparation method are the same as those in Example 1, except that:
[0023] S1: Stir at a speed of 400 r / min, 1200 r / min, and 3000 r / min from slow to fast for 5 min, 1 min, and 2 min respectively;
[0024] S2: The curing agent is EPIKURE 3072 amidoamine curing agent. After adding the curing agent, the mixture is stirred at a speed of 3000 r / min for 2 minutes, and then vacuum degassing is performed for 60 minutes.
[0025] S3: The spacing between the copper electrodes is 9 mm, the heating temperature of the vacuum oven is 50 °C, and the heating time is 30 h.
[0026] Example 3
[0027] The specific steps of the preparation method are the same as those in Example 1, except that:
[0028] S1: Stir at a speed of 600 r / min, 800 r / min, and 1500 r / min from slow to fast for 1 min, 5 min, and 10 min respectively;
[0029] S2: The curing agent is a combination of EPIKURE 3046 amidoamine curing agent and EPIKURE 3072 amidoamine curing agent (mass ratio = 1:1). After adding the curing agent, stirring is performed at a speed of 1500 r / min for 10 minutes, and then vacuum degassing is performed for 20 minutes.
[0030] S3: The spacing between the copper electrodes is 6 mm, the heating temperature of the vacuum oven is 100 °C, and the heating time is 10 h.
[0031] Example 4
[0032] The specific steps of the preparation method are the same as those in Example 1, except that:
[0033] S1: The content of nano boron nitride is 15wt%; stirring at a speed of 600r / min, 800r / min, and 1500r / min from slow to fast for 1min, 5min, and 10min respectively;
[0034] S2: The curing agent is EPIKURE 3046 amidoamine curing agent. After adding the curing agent, stirring is performed at a speed of 1500 r / min for 10 minutes, and then vacuum degassing is performed for 20 minutes.
[0035] S3: The spacing between the copper electrodes is 1 mm, the heating temperature of the vacuum oven is 100 °C, and the heating time is 10 h.
[0036] Example 5
[0037] The specific steps of the preparation method are the same as those in Example 1, except that:
[0038] S1: The content of nano-boron nitride is 20wt%; stirring is performed at a speed of 550r / min, 1100r / min, and 2500r / min from slow to fast for 2min, 2min, and 4min respectively;
[0039] S2: The curing agent is EPIKURE 3072 amidoamine curing agent. After adding the curing agent, stirring is performed at a speed of 2500 r / min for 4 minutes, and then vacuum degassing is performed for 25 minutes.
[0040] S3: The spacing between the copper electrodes is 10 mm, the heating temperature of the vacuum oven is 60 °C, and the heating time is 25 h.
[0041] Comparative Example 1
[0042] S1: The content of nano boron nitride is 25wt%; the mixture of nano boron nitride and epoxy resin is stirred and dispersed by a planetary mixer. The mixture of nano boron nitride particles and epoxy resin is stirred and dispersed once by a planetary mixer combining revolution and rotation: stirring at a speed of 2000r / min for 6min.
[0043] S2: Same as Example 1.
[0044] S3: Same as Example 1.
[0045] Comparative Example 2
[0046] S1: The content of nano boron nitride is 25wt%; the steps are the same as those in Example 1.
[0047] S2: Same as Example 1.
[0048] S3: placing the mold in a vacuum oven for heating to accelerate the curing process. The heating temperature of the vacuum oven is 80° C. and the heating time is 20 h (without applying an electric field).
[0049] Comparative Example 3
[0050] S1: The content of nano boron nitride is 30wt%, and the rest is the same as Example 1.
[0051] S2: Same as Example 1.
[0052] S3: placing the mold in a vacuum oven for heating to accelerate the curing process. The heating temperature of the vacuum oven is 80° C. and the heating time is 20 h (without applying an electric field).
[0053] The performance of the above examples and comparative examples is shown in Table 1:
[0054] Table 1 Performance of Examples and Comparative Examples
[0055]
[0056] It can be seen from the above embodiments that the use of a curing agent with better curing performance, the composite material is fully stirred and an external DC electric field during the curing process of the material can significantly improve the thermal conductivity of the composite material and the dielectric constant of the composite material, and the thermal conductivity and electrical resistance of the material are improved together. The amidoamine curing agent used in the present invention can be cross-linked with the epoxy group in the epoxy resin to form a stable three-dimensional network structure that is not easily dissolved and dissolved, so that the defects in the composite material are as few as possible, so its dielectric constant is relatively high, and the curing agent can promote the BN in the epoxy resin to form a heat-conducting chain, thereby reducing the thermal resistance of the composite material, and improving its thermal conductivity. And the curing performance of EPIKURE 3046 amidoamine curing agent is better than EPIKURE3072 amidoamine curing agent, and the composite material thermal conductivity using EPIKURE3046 amidoamine curing agent is improved higher, and the dielectric constant is also relatively high. The composite material with a BN content of 15-25% and electric field orientation used in this paper has a thermal conductivity of 0.931 W / (m·K) and a relative dielectric constant of 7.51, which are higher than those of the composite material with a BN content of 30% and not oriented by electric field. The material is also easier to stir during preparation.
[0057] Finally, it should be noted that the above is only a preferred embodiment of the present invention and does not limit it. Although this patent is described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions recorded in the aforementioned embodiments or to replace some of the technical features therein with equivalents. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing a nano boron nitride / epoxy resin composite material with electric field induced boron nitride nanosheet orientation, characterized in that: The steps include: S1: using a planetary mixing device to stir and disperse the mixture of nano boron nitride and epoxy resin; S2: adding a curing agent to the stirred and dispersed mixture of nano boron nitride and epoxy resin, performing vacuum degassing and placing the mixture in a mold; S3: The arrangement direction of the boron nitride nanosheets in the mixture is regulated by a direct current electric field during the curing process. At the same time, the mold is placed in a vacuum oven for heating to accelerate the curing process. In step S1, the content of nano boron nitride is 25wt%; a planetary mixing device combining revolution and rotation is used to stir and disperse the mixture of nano boron nitride particles and epoxy resin for multiple times: stirring at a speed of 400-600r / min, 800-1200r / min, and 1500-3000r / min from slow to fast for 1-5min, 1-5min, and 2-10min, respectively, so that the nano boron nitride particles can be evenly dispersed in the epoxy resin; In step S2, the curing agent is one or a combination of EPIKURE 3046 amidoamine curing agent and EPIKURE 3072 amidoamine curing agent. After adding the curing agent, stirring is performed at a speed of 1500 to 3000 r / min for 2 to 10 minutes, and then vacuum degassing is performed for 20 to 60 minutes.
2. The method for preparing a nano boron nitride / epoxy resin composite material with electric field induced boron nitride nanosheet orientation according to claim 1, characterized in that: In step S1, the content of nano boron nitride is 25wt%; stirring is performed at a speed of 500r / min, 1000r / min, and 2000r / min from slow to fast for 3min, 3min, and 6min respectively so that the nano boron nitride particles can be evenly dispersed in the epoxy resin.
3. The method for preparing a nano boron nitride / epoxy resin composite material with electric field induced boron nitride nanosheet orientation according to claim 1, characterized in that: In step S2, the curing agent is EPIKURE 3046 amidoamine curing agent. After adding the curing agent, stirring is performed at a speed of 2000 r / min for 6 minutes, and then vacuum degassing is performed for 30 minutes.
4. The method for preparing a nano boron nitride / epoxy resin composite material with electric field induced boron nitride nanosheet orientation according to claim 1, characterized in that: In step S3, during the curing process of the nano-boron nitride / epoxy resin composite material, copper electrodes with a spacing of 1 to 10 mm are placed inside the mold, and a DC voltage is applied to the electrodes to achieve alignment and orientation of the boron nitride nanosheets in the composite material in the direction of the electric field intensity.
5. The method for preparing a nano boron nitride / epoxy resin composite material with electric field induced boron nitride nanosheet orientation as claimed in claim 4, characterized in that: In step S3, the spacing between the copper electrodes placed inside the mold is 3 mm.
6. The method for preparing a nano-boron nitride / epoxy resin composite material with electric field induced orientation of boron nitride nanosheets as claimed in claim 1, characterized in that: In step S3, the heating temperature of the vacuum oven is 50-100° C., and the heating time is 10-30 hours.
7. The method for preparing a nano-boron nitride / epoxy resin composite material with electric field induced orientation of boron nitride nanosheets as claimed in claim 6, characterized in that: In step S3, the heating temperature of the vacuum oven is 80° C. and the heating time is 20 h.
Citation Information
Patent Citations
Preparation method of boron nitride-silicon rubber composite material
CN102717454A